Supervisory Role of The Republic of Indonesia Judicial Commission Liaison Office in The Province South Kalimantan - Agnes Gunawan Putri Mega Wijaya; Ergina Faralita (Interdisciplinary Explorations in Research Journal, 2023)
Abstract This research aims to determine the role of the Judicial Commission Liaison. The Judicial Commission Liaison is a specific institution regulated in Judicial Commission Regulation Number 1 of 2017 concerning the formation, structure and work procedures of Judicial Commission Liaison in the regions. Its function is to assist the implementation of the duties of the Judicial Commission of the Republic of Indonesia at the regional level. The South Kalimantan Judicial Commission Liaison was established in 2022. The South Kalimantan Judicial Commission Liaison is still facing a number of obstacles, both from internal and external factors of the institution. This research uses empirical legal research. The nature of this research is qualitative, namely a research process with results in the form of analytical descriptive data. Based on the method used, the research results were obtained as follows: first, the role of the South Kalimantan Judicial Commission Liaison with Judges regarding monitoring and supervision has been maximized in carrying out their duties, in accordance with Article 20 of Law Number 18 of 2011 in the context of maintaining and upholding the honor, nobility and behavior of judges, the Liaison Role of the South Kalimantan Judicial Commission reflects efforts to maintain the honor, nobility and behavior of judges in the region. With community involvement in providing reports and openness in the monitoring process. Several problems that need to be updated include: (i) the lack of human resources available at the Judicial Commission Liaison for the South Kalimantan region, (ii) the limited authority possessed by the Judicial Commission Liaison, and (iii) lack of optimization of the budget given to the institution the. Keywords: Judicial Commission, Judicial Commission Liaison, Judge Supervision Abstrak Penelitian ini bertujuan untuk mengetahui peran Penghubung Komisi Yudisial Penghubung Komisi Yudisial merupakan lembaga yang spesifik diatur dalam Peraturan Komisi Yudisial Nomor 1 Tahun 2017 tentang pembentukan, susunan, dan tata kerja Penghubung Komisi Yudisial di daerah. Fungsinya adalah membantu pelaksanaan tugas Komisi Yudisial Republik Indonesia di tingkat daerah. Penghubung Komisi Yudisial wilayah Kalimantan Selatan berdiri sejak tahun 2022. Penghubung Komisi Yudisial Kalimantan Selatan masih menghadapi sejumlah kendala, baik itu dari faktor internal maupun eksternal lembaga. Penelitan ini menggunakan penelitian hukum empiris. Adapun sifat penelitan ini adalah kualitatif yaitu suatu proses penelitian dengan hasil dalam bentuk data deskriptif analitis.Berdasarkan metode yang digunakan diperoleh hasil penelitan sebagai berikut: pertama, peran Penghubung Komisi Yudisial Kalimantan Selatan terhadap Hakim mengenai pemantauan dan pengawasan sudah maksimal dalam menjalankan tugasnya, sesuai dengan Pasal 20 Undang - Undang Nomor 18 Tahun 2011 dalam rangka menjaga dan menegakkan kehormatan, keluhuran martabat, serta perilaku hakim, Peran Penghubung Komisi Yudisial Kalimantan Selatan mencerminkan upaya untuk menjaga kehormatan, keluhuran martabat, dan perilaku hakim di wilayah tersebut. Dengan keterlibatan masyarakat dalam memberikan laporan dan keterbukaan dalam proses pengawasan. Beberapa masalah yang perlu diperbaharui antara lain adalah: (i) kurangnya jumlah sumber daya manusia yang tersedia di Penghubung Komisi Yudisial wilayah Kalimantan Selatan, (ii) keterbatasan wewenang yang dimiliki oleh Penghubung Komisi Yudisial, dan (iii) kurangnya optimalisasi anggaran yang diberikan kepada lembaga tersebut. Kata kunci: Komisi Yudisial, Penghubung Komisi Yudisial, Pengawasan Hakim This is an open access article under the CC BY-NC-SA license.